ETNOZOOLOGI UNTUK RITUAL ADAT DAN MISTIS MASYARAKAT DAYAK ELLA DI DESA SUNGAI LABUK KECAMATAN ELLA HILIR KABUPATEN MELAWI - Ramadiana, .; Anwari, Sofwan; Yani, Ahmad (Universitas Tanjungpura, 2018)
Utilization of flora and fauna have been managed by various ethnic in kalimantan for the needs of their life. One of the original ethnic comunity in West Kalimantan is the Dayak EllaÂ located in Sungai Labuk Village, Ella Hilir Sub-District, Melawi Regency. The Dayak Ella community also has diversity in the utilization of fauna for food, medicines, traditional and supernatural ceremonies. The purpose of this research is to get data of the types of animals that are used for custom and mystical rituals and how to use them by Dayak Ella community. This research uses data collection method that is by field survey, interview and direct observation in the field while for data collection technique that is by snowball sampling technique that is by determining the key respondent to then determine other respondent based on information from previous respondent, so also for so on. The results showed that the number of animals used for custom or mystical rituals by the Ella Dayak community in Sungai Labuk Village Ella Hilir Sub-District Melawi District, which is 5 species of animals from 5 families, on average each family consists of only 1 species. The parts of animals used for this custom or mystical ritual are the whole body, head, blood, nails, fangs, liver, eggs, blood, and fur. Utilization of these animals use such a way of giving the whole body of both meat and blood of the animal for offerings on the spirits, there is also part of the animal such as fangs or nails that serve as a symbol or other sign.Keyword: Customary and Mystical Rituals, Dayak Ella, Ethnozoology